Oxytocin Promotes Accurate Fear Discrimination and Adaptive Defensive Behaviors - Olivera-Pasilio, Valentina; Dabrowska, Joanna (Frontiers in Neuroscience, 2020)
The nonapeptide, oxytocin (OT), known for its role in social bonding and attachment formation, has demonstrated anxiolytic properties in animal models and human studies. However, its role in the regulation of fear responses appears more complex, brain site-specific, sex-specific, and dependent on a prior stress history. Studies have shown that OT neurons in the hypothalamus are activated during cued and contextual fear conditioning and during fear recall, highlighting the recruitment of endogenous oxytocin system in fear learning. OT is released into the extended amygdala, which contains the central nucleus of the amygdala (CeA) and the bed nucleus of the stria terminalis (BNST), both critical for the regulation of fear and anxiety-like behaviors. Behavioral studies report that OT in the CeA reduces contextual fear responses; whereas in the BNST, OT receptor (OTR) neurotransmission facilitates cued fear and reduces fear responses to un-signaled, diffuse threats. These ostensibly contrasting behavioral effects support growing evidence that OT works to promote fear discrimination by reducing contextual fear or fear of diffuse threats, yet strengthening fear responses to imminent and predictable threats. Recent studies from the basolateral nucleus of the amygdala (BLA) support this notion and show that activation of OTR in the BLA facilitates fear discrimination by increasing fear responses to discrete cues. Also, OTR transmission in the CeA has been shown to mediate a switch from passive freezing to active escape behaviors in confrontation with an imminent, yet escapable threat but reduce reactivity to distant threats. Therefore, OT appears to increase the salience of relevant threat-signaling cues yet reduce fear responses to un-signaled, distant, or diffuse threats. Lastly, OTR signaling has been shown to underlie emotional discrimination between conspecifics during time of distress, social transmission of fear, and social buffering of fear. As OT has been shown to enhance salience of both positive and negative social experiences, it can also serve as a warning system against potential threats in social networks. Here, we extend the social salience hypothesis by proposing that OT enhances the salience of relevant environmental cues also in non-social contexts, and as such promotes active defensive behaviors.